Hybrid Plasmonic and Pyroelectric Harvesting of Light Fluctuations. Issue 11 (22nd March 2018) - Shiran Chaharsoughi, Mina; Tordera, Daniel; Grimoldi, Andrea; Engquist, Isak; Berggren, Magnus; Fabiano, Simone; Jonsson, Magnus P.
Abstract: State‐of‐the‐art solar energy harvesting systems based on photovoltaic technology require constant illumination for optimal operation. However, weather conditions and solar illumination tend to fluctuate. Here, a device is presented that extracts electrical energy from such light fluctuations. The concept combines light‐induced heating of gold nanodisks (acting as plasmonic optical nanoantennas), and an organic pyroelectric copolymer film (poly(vinylidenefluoride‐ co ‐trifluoroethylene)), that converts temperature changes into electrical signals. This hybrid device can repeatedly generate current pulses, not only upon the onset of illumination, but also when illumination is blocked. Detailed characterization highlights the key role of the polarization state of the copolymer, while the copolymer thickness has minor influence on performance. The results are fully consistent with plasmon‐assisted pyroelectric effects, as corroborated by combined optical and thermal simulations that match the experimental results. Owing to the tunability of plasmonic resonances, the presented concept is compatible with harvesting near infrared light while concurrently maintaining visible transparency. Abstract : A hybrid plasmonic pyroelectric device is presented for harvesting energy from temporal light fluctuations. Plasmonic gold nanodisks act as light‐triggered nanoscale heat sources and convert optical energy fluctuations to thermal energy fluctuations. This induces temperature changes in a copolymer pyroelectric layer (poly(vinylidenefluoride‐co‐trifluoroethylene), P(VDF‐TrFE)), resulting in electrical output and energy harvesting of the light intensity fluctuations.